THE EFFECT OF LIQUID SMOKE ON THE QUALITY AND OMEGA-3 FATTY ACIDS CONTENT OF TUNA FISH (Euthynnus affinis) - Fronthea Swatawati; Takeshi Suzuki; Eko Nurcahya Dewi (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Introduction : the problem faced in smoking fish is primarily related to deterioration of lipid caused by oxidation, that may cause of omega-3 fatty acid content in fish. This research was aimed at investigating the effect of different method of smoking fish to the organoleptic value, proximate composition and omega-3 fatty acid content. The experiment was carried out in The Laboratory of Coastal Zone Ecodevelopment, Diponegoro University, Jepara. Analysis of omega-3 fatty acid was conducted using Shimadzu Gas Chromathography in The Laboratory of Food Science and Technology, Tokyo University of Fisheries, Japan. Material and Method : a randomized design was used in this study; filleted skipjack tuna (Eutynnus affinis); approximately 125 gr in weight and about 25 cm in length was used in both coconut shell for the traditional method and liquid smoke from Giulini Chemii for modern method. The temperature of the smoking process was between 40 – 80 °C. Sensory test and proximate composition were determined in order to support an omega-3 fatty acid analysis. Result and Discussion : the average value of sensory test of traditional smoked tuna was between 3.00 – 8.33; liquid smoked tuna was between 6.67 – 9.00. the protein composition was 38.98% and lipid was 2.71% for the traditional product and 32.21% and 2.06% were obtained in liquid smoked tuna. Analysis of DHA resulted in 17.6% (traditional) and 20.9 (liquid). The results showed a significant difference between two products. The product of liquid smoked fish had better appearance, longer shelf life and higher omega-3 fatty acid content.